2010
DOI: 10.5336/medsci.2008-9283
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Services Utilization by the General Population in the Center of Kayseri, Turkey

Abstract: A AB BS S T TR RA AC CT T O Ob bj je ec ct ti iv ve e: : Pre vi o us stu di es ha ve re ve a led the so ci al, eco no mic, and psycho lo gi cal fac tors that inf lu en ce con sul ting be ha vi o ur; ho we ver the he alth ser vi ces uti li za ti on by the ge ne ral po pu la ti on are seldomly stu di ed. The aim of this study was to exa mi ne the le vel of he alth ser vi ces uti li za ti on and the ef fects of pre dis po sing, enab ling, and ne ed fac tors on Tur kish ge ne ral po pu la ti on. M Ma at te er ri i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
(32 reference statements)
3
7
0
1
Order By: Relevance
“…We found in our study that having health insurance increased utilization of healthcare services, but it was not significantly effective. With this aspect, our study was in agreement with other studies that were carried out in Turkey (1,2,19). We may state that this could have been caused by state policies such as elderly care salaries for those who do not have pensions or private health insurance, free health and care assistance for the elderly, or that the elderly may also receive healthcare services by making payments without receiving any healthcare insurance or assistance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found in our study that having health insurance increased utilization of healthcare services, but it was not significantly effective. With this aspect, our study was in agreement with other studies that were carried out in Turkey (1,2,19). We may state that this could have been caused by state policies such as elderly care salaries for those who do not have pensions or private health insurance, free health and care assistance for the elderly, or that the elderly may also receive healthcare services by making payments without receiving any healthcare insurance or assistance.…”
Section: Discussionsupporting
confidence: 92%
“…Cotingting (2019) also found that the variable of health insurance does not have an effect on the demand, while some studies determined that increased income status is a significant variable that increases the demand (1,2,(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In the study conducted by Senol et al in 2010 in Kayseri, it was determined that the elderly, female patients and the illiterate people utilized the health services significantly more, and when considered in terms of occupations, the housewives and retired people applied to health centers more frequently like in our study. 20 The greater number of applications to the first step by the housewives may be due to the fact that women make more application since men are at work during the business hours and that the children are taken to the doctor by mothers. Scores of the patients whose occupation was farming were higher compared to other groups of occupation ( P <0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Uzak çadır bölgelerinde kalanların özellikle birinci basamak sağlık hizmetlerini daha çok kullandığı belirlendi. Literatürde sağlık hizmeti kullanımının mesafeden etkilendiğini belirten çalışmalar bulunmaktadır (30)(31)(32)(33) Birinci basamak sağlık kuruluşlarına başvuran MTİ'lerinde en çok görülen sağlık sorunları sindirim sistemi hastalıkları, solunum sistemi hastalıkları, pediatrik hastalıklar ve kas-iskelet sistemi hastalıkları idi. MTİ'nin yoğun olarak yaşadığı Türkiye'nin Güneydoğu Anadolu Bölgesi'nde yapılan çalışmalarda en sık görülen hastalıklar üst solunum yolu hastalıkları ve kas-iskelet sistemi hastalıkları olarak bildirilmiştir (11,12) .…”
Section: Gereç Veunclassified